GAMBARAN PENGETAHUAN KELUARGA TENTANG GASTRITIS DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2023 - Indra Hizkia Perangin angin; Alde Casanova Naibaho, (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Knowledge is one of the main sources of progress or failure of a nation's civilization, and begins with people's attention to science. Knowledge is very important and needs attention to live a better life. Gastritis is a disease that is often found, even spread throughout the world and it is estimated that there are billions of sufferers of gastritis. This study aims to determine family knowledge about gastritis at Santa Elisabeth Hospital Medan in 2023. This study used a quantitative method where data was collected by distributing questionnaires with 18 statements so as to explore the knowledge of families of gastritis patients. This type of research is descriptive with a total population of 46 people. Sampling was carried out by purposive sampling technique and using the slovin formula, with a total of 32 respondents. The results showed that 18 respondents (58.1%) had good knowledge of the patient's family at Santa Elisabeth Hospital Medan, 11 respondents (35.5%) had enough knowledge, and 2 respondents (6.5%) had less knowledge. . It was concluded that the majority of families of gastritis patients at Santa Elisabeth Hospital Medan were categorized as "good" in knowing about gastritis. In this study, it was found that the knowledge of respondents was influenced by education and information obtained from the work environment, experience, social and mass media. With this knowledge, respondents can find out information about, understanding, etiology, classification, pathophysiology, risk factors, signs and symptoms, management and prevention of gastritis. It is hoped that the patient's family should share knowledge with the people around them and increase knowledge about gastritis and by seeking information from various available sources, or from people who have experience in preventing gastritis, can also through health workers in their area.